The Essence of Ontology in Islamic Philosophy: Discourse on Wujūd in al-Ḥikmat al-Mashā'iyyat and al-Ḥikmat al-Ishrāq - Miswari, Miswari (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
This article seeks to analyze the concept of wujūd in Islamic philosophy, including the Peripatetic (al-Ḥikmat al-Mashā’iyyat) and Illuminationist (al-Ḥikmat al-Ishrāq) schools. The study employs a discourse analysis approach, using data collected from an analysis of Islamic philosophy literature with a focus on the concept of wujūd in these two schools. The findings of the study show that despite using the same term, the concept of external reality has different meanings in different schools of Islamic philosophy. The Peripatetic school interprets wujūd as the basis of reality, but its extension varies depending on the differences in māhiyat (essence). The Illuminationist school, on the other hand, interprets wujūd as an addition to external reality, as the fundamental element is māhiyat. One of the novel contributions of this study is to highlight the sensitivity of the concept of essence in Islamic ontology, as evidenced by the different meanings of wujūd in the two schools of Islamic philosophy. However, both schools agree that wujūd is manifested as a mental reality, a predication for māhiyat. In mental reality, the fundamental element is māhiyat.